Stabilization with Internal Loop for Infinite-Dimensional Discrete Time-Varying Systems - Nai-feng Gan; Yu-feng LU; Ting Gong (Discrete Dynamics in Nature and Society)
The concepts of stabilization with internal loop are analyzed for well-posed transfer functions. We obtain some sufficient and necessary conditions such that a stabilizing controller with internal loop stabilizes plant L. We also analyze two special subclasses of stabilizing controllers with internal loop, called canonical and dual canonical controllers, and show that all stabilizing controllers can be parameterized by a doubly coprime factorization of the original transfer function.